The Application of Spreadsheet Model Based on Queuing Network to Optimize Capacity Utilization in Product Development - Marsudi, Muhammad; Abdul Wahab, Dzuraidah; Che Haron, Che Hasan (International Journal of Integrated Engineering, 2009)
Modeling of a manufacturing system enables one to identify the effects of key design parameters on the system performance and as a result make the correct decision. This paper proposes a manufacturing system modeling approach using computer spreadsheet software, in which a static capacity planning model and stochastic queuing model are integrated. The model was used to optimize the existing system utilization in relation to product design. The model incorporates a few parameters such as utilization, cycle time, throughput, and batch size. It is predicted that design changes initiated as a result of analysis using the model reduced subsequent manufacturing costs significantly and also can reduce the launch program by a few years, because confidence in the model justified the commissioning of full-scale manufacturing equipment when the product was still only at the concept stage.